Education in Vascular Access. Issue 2 (25th February 2013) - Moist, Louise M.; Lee, Timmy C.; Lok, Charmaine E.; Al‐Jaishi, Ahmed; Xi, Wang; Campbell, Vern; Graham, Janet; Wilson, Barb; Vachharajani, Tushar J.
Abstract The successful creation and use of an arteriovenous vascular access (VA) requires a coordinated, educated multidisciplinary team to ensure an optimal VA for each patient. Patient education programs on VA are associated with increased arteriovenous VA use at dialysis initiation. Education should be tailored to patient goals and preferences with the understanding that experiential education from patient to patient is far more influential than that provided by the healthcare professional. VA education for the nephrologist should focus on addressing the systematic and patient‐level barriers in achieving a functional VA, with specific components relating to VA creation, maturation, and cannulation that consider patient goals and preferences. A deficit in nursing skills in the area of assessment and cannulation can have devastating consequences for hemodialysis patients. Delivery of an integrated education program increases nurses' knowledge of VA and development of simulation programs or constructs to assist in cannulation of the VA will greatly facilitate the much needed skill transfer. Adequate VA surgical training and experience are critical to the creation and outcomes of VA. Simulations can benefit nephrologists, dialysis nurses surgeons, and interventionalists though aiding in surgical creation, understanding of the physiology and anatomy of a dysfunctional VA, and practicing cannulation techniques. All future educational initiatives must emphasize the importance of multidisciplinary care to attain successful VA outcomes.